2013
DOI: 10.1021/jp410123d
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Transport Properties of Poly[2-(methacryloyloxy)ethyl]trimethylammonium Chloride Brushes Resulting from Ion Specific Effects

Abstract: Combined use of electrochemical techniques (electrochemical impedance spectroscopy and cyclic voltammetry) and quartz crystal microbalance with dissipation allowed to resolve separately the thermal effects on diffusion and electron-transfer steps of the electrochemical reaction of the [Fe(CN) 6 ] 3−/4− redox couple at a Au electrode modified with poly[2-(methacryloyloxy)ethyl]trimethylammonium chloride (PMETAC) brushes. Arrhenius-type dependences of the kinetic constant and the diffusion coefficient with tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…45 It was also shown that PMETAC brushes, swelling to conformations accommodating 67% water molecules, lost 17% water during collapse in 0.1 M NaCl, whereas the collapse in 0.1 M NaClO 4 led to a loss of 54% of associated water. 45 Similar observations were reported for other strong polycationic brushes such as p o l y ( v i n y l b e n z y l t r i m e t h y l a m m o n i u m c h l o r i d e ) (PVBTMAC). 46 QCM-D data gave evidence for dramatic changes in brush hydration upon exposure to chaotropic ions.…”
Section: ■ Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…45 It was also shown that PMETAC brushes, swelling to conformations accommodating 67% water molecules, lost 17% water during collapse in 0.1 M NaCl, whereas the collapse in 0.1 M NaClO 4 led to a loss of 54% of associated water. 45 Similar observations were reported for other strong polycationic brushes such as p o l y ( v i n y l b e n z y l t r i m e t h y l a m m o n i u m c h l o r i d e ) (PVBTMAC). 46 QCM-D data gave evidence for dramatic changes in brush hydration upon exposure to chaotropic ions.…”
Section: ■ Introductionmentioning
confidence: 97%
“…In comparison, strong polyelectrolytes do not typically respond to variations in pH but present complex conformational changes in response to variations in electrolyte type and ionic strength. For example, polycationic poly­((2-methacryloyloxy)­ethyl trimethylammonium chloride) (PMETAC) brushes display different swelling behavior in the presence of chaotropic anions, such as perchlorates, in comparison to more kosmotropic ions such as chlorides . It was also shown that PMETAC brushes, swelling to conformations accommodating 67% water molecules, lost 17% water during collapse in 0.1 M NaCl, whereas the collapse in 0.1 M NaClO 4 led to a loss of 54% of associated water .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyelectrolyte brushes are promising approaches to the construction of highly charged interfacescharged macromolecules grafted densely onto the interfaces, including solid–liquid, liquid–liquid, and air–liquid interfaces, by physisorption and chemisorption. , Intensive research studies have been conducted continuously on polyelectrolyte brushes, the smart and responsive interfacial materials, and believed to be perspective candidates of functional surfaces for bio-lubrication, , reactors of small scale, smart drug delivery, , controlling devices of micro-fluids, and so forth. Despite the unique and promising properties and functionalities of polyelectrolyte brushes, the physical mechanism of their structure and responsive behavior has been drawing considerable research attention, both theoretically and experimentally. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the PNIPAM/PAEtMA‐based WAL has a ‘thicker wall’ and larger pore size in comparison with the PNIPAM/NPs‐based LHL. This result may be attributed to the lower glass transition temperature ( T g) of PAEtMA, resulting in a ‘slower’ solidification process in the freezing dry [23] . We also observed a clear boundary between the two layers (Figure 3C) and the connection is stable without sign of detachment.…”
Section: Resultsmentioning
confidence: 75%